Censorship: Twitter/X (Brazil) - Voidly (2024)
WARNING severity censorship detected in Brazil. Confidence: 75%. Data sourced from CensoredPlanet.
Censorship Incident ID: BR-2024-0001
Keywords: censorship; BR; censorship; warning